DIAGNOSTIC ACCURACY OF PI-RADS FOR PROSTATIC MALIGNANCY; NON-INVASIVE ASSESSMENT OF THE PROSTATE GLAND - Hanif , Hina; Amin, Ayesha; Altaf, Humera; Meraj, Lubna; Usmani, Fareya; Shams, Nadia (Journal of Ayub Medical College Abbottabad, 2024)
Background: The use of multi-parametric (mp) MRI for the detection and characterization of prostate lesions has evolved over the last decade. This study was conducted to determine the diagnostic accuracy of Prostate Imaging Reporting and Data System (PI-RADS) in diagnosing prostatic malignancy, taking histopathology as gold standard. Methods: A cross-sectional validation study was conducted in Dept. of Radiology, Benazir Bhutto Hospital Rawalpindi from March 10th to June 10th 2024. Total 120 patients with suspected prostate malignancy (50–80 years’ age) were included. Patients with known allergy to Gadolinium based MRI contrast agent, Impaired renal function (GFR<30 ml/min) and claustrophobia were excluded. The MRI examinations were done in all cases on 1.5 Tesla MRI unit with body coil coupled to endorectal coil in the supine position. The PI-RADS findings were interpreted by consultant radiologist for prostatic malignancy. All patients were undergone biopsy in the concerned ward and tissue was sent to institutional laboratory for histopathology. Histopathology report was compared with PI-RADS findings. Results: The Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of PI-RADS in diagnosing prostatic malignancy, taking histopathology as gold standard was 85.51%, 84.31%, 88.06%, 81.13% and 85.0% respectively. Conclusion: This study concluded that PI-RADS is the non-invasive modality of choice with high diagnostic accuracy in detecting prostate cancer, and has dramatically improved our diagnostic and prognostic ability.